A high-performance aging-resistant rubber and preparation method thereof
By reacting phenol anti-aging agent with gamma-glycidyl etheroxypropyl trimethoxysilane in brominated butyl rubber, the stability problem caused by excessive reactivity of brominated butyl rubber is solved, and the anti-aging and mechanical properties of the rubber are improved.
Patent Information
- Application Number
- CN202510070999.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Brominated butyl rubber is too reactive during processing, causing anti-aging agents to trigger cross-linking reactions and destroy the stability of the rubber. The prior art depends on the anti-aging properties of brominated butyl rubber itself, which still needs to be improved.
Phenol anti-aging agents are used, which have at least triphenylamine groups in the structure. The structure of anti-aging agent-coupling agent-filler is formed by reacting with γ-glycidyl etheroxypropyl trimethoxysilane, which improves the dispersion of carbon nanotubes and carbon black, and grafts the anti-aging agent onto the filler to improve the anti-aging and mechanical properties of the rubber.
It improves the stability and anti-aging properties of brominated butyl rubber, enhances its mechanical properties, reduces the amount of anti-aging agent used, and improves the dispersion of functional fillers, and improves the overall performance of rubber.
Smart Images

Figure BDA0005245696660000031 
Figure BDA0005245696660000081 
Figure BDA0005245696660000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber, and in particular relates to a high-performance anti-aging rubber and a preparation method thereof. Background Art
[0002] Bromobutyl rubber (BIIR) is the bromination product of butyl rubber (IIR). Butyl rubber is a copolymer of isobutylene and a small amount of isoprene produced by cationic polymerization at low temperature. Bromobutyl rubber is obtained by introducing bromine atoms into butyl rubber through bromination reaction. The introduction of bromine atoms changes the chemical structure of butyl rubber. In the molecular chain of brominated butyl rubber, bromine atoms are mainly distributed near the double bond position of the isoprene unit. This structure allows brominated butyl rubber to retain some excellent properties of butyl rubber, such as excellent air tightness, chemical corrosion resistance and shock absorption performance, and add new properties, such as better vulcanization activity and compatibility with other rubbers or materials. During the processing of brominated butyl rubber, the presence of halogen atoms in its molecular structure enhances its reactivity. The energy required to break the carbon-bromine bond is lower than the energy required to break the carbon-chlorine bond and the carbon-carbon bond. Therefore, compared with butyl rubber and chlorobutyl rubber, brominated butyl rubber shows higher reactivity with rubber processing aids. However, this also brings some disadvantages. Its reactivity is too high, and the antioxidant will cause cross-linking reaction of the brominated butyl rubber matrix, thereby destroying the stability of the rubber.
[0003] For example, CN111019250A provides an anti-aging method for brominated butyl rubber, characterized in that a liquid antioxidant is added in the post-treatment drying section; the pH of the polymerization flash tank is controlled to be 7.0-9.0, and the pH of the bromination flash tank is controlled to be 7.5-9.0; the liquid antioxidant is one or more of FT-NOX 3036, B7029, 1520 and 1135. This application uses a liquid antioxidant, and the filling method and filling position of the antioxidant are changed. However, the antioxidant has an impact on the stability of brominated butyl rubber.
[0004] For example, CN109776979A provides a carbon nanotube-doped ionic liquid modified butyl rubber elastomer, wherein the butyl rubber elastomer is a carbon nanotube-doped imidazole ionic liquid modified brominated butyl rubber, which is prepared by mixing brominated butyl rubber, imidazole molecular additives and carbon nanotube powder. The butyl rubber elastomer has a high degree of ionization modification and good carbon nanotube dispersion performance, and does not require further vulcanization treatment. The prepared carbon nanotube-doped ionic liquid modified butyl rubber elastomer has a tensile strength of more than 15MPa and an elongation at break of nearly 10 times. The prepared carbon nanotube-doped ionic liquid modified butyl rubber elastomer has a dielectric constant of more than 20 and a conductivity of 10 at room temperature and a frequency of 100Hz. -5 S / cm, and has high self-healing ability under hot pressing. However, this application still relies on the anti-aging properties of bromobutyl rubber itself, which still needs to be improved.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a high-performance aging-resistant rubber and a preparation method thereof. The present invention has excellent aging-resistant performance and excellent mechanical properties at the same time, and the rubber obtained by the present invention has good stability and is widely used.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] In a first aspect, an embodiment of the present invention provides a high-performance anti-aging rubber, including brominated butyl rubber and an antioxidant;
[0009] Relative to 100 parts by weight of brominated butyl rubber, the content of the antioxidant is 0-5 parts by weight;
[0010] The antioxidant is a phenolic antioxidant, and the phenolic antioxidant has at least a triphenylamine group in its structure.
[0011] In a preferred embodiment, the antioxidant has a structure as shown in the following formula (1):
[0012]
[0013] The invention defines the above antioxidant, which is not easy to react with the rubber matrix due to the skeleton structure of the triarylamine, thereby improving the aging performance and strengthening the stability of the rubber.
[0014] The invention defines that the diphenylamine skeleton is connected to phenol, and the hydrogen atoms on the amino groups in the diphenylamine molecules are relatively active and can be easily oxidized to generate nitroxide free radicals. The nitroxide free radicals can combine with the active free radicals (generated during the oxidation process of the protected material to interrupt the oxidation chain reaction and play an antioxidant role. The hydrogen atoms on the phenolic hydroxyl groups on phenol are relatively active. When encountering free radicals, the phenolic hydroxyl groups can provide hydrogen atoms and form relatively stable phenoloxy free radicals by themselves. This process interrupts the oxidation chain reaction because the generated phenoloxy free radicals are relatively stable and will not easily trigger new oxidation reactions. In addition, triphenylamine is connected to the diphenylamine skeleton, and the steric hindrance generated by the tert-butyl group on the structure of triphenylamine can make the reaction of the antioxidant and the free radical more controllable, strengthen the chemical stability, and improve the stability of the brominated butyl rubber.
[0015] In a preferred embodiment, the rubber includes 10-20 parts by weight of the functional filler relative to 100 parts by weight of the brominated butyl rubber.
[0016] In a preferred embodiment, the preparation method of the functional filler is as follows:
[0017] S1, mixing carbon nanotubes with anhydrous ethanol, uniformly dispersing by ultrasonication, then adjusting the pH to 3-5 with oxalic acid solution, then adding potassium permanganate, and obtaining carboxylated carbon nanotubes after reaction;
[0018] S2, mixing the antioxidant and γ-glycidyloxypropyltrimethoxysilane, and adding carboxylated carbon nanotubes and carbon black after reflux reaction, cooling and centrifuging after reaction to obtain a functional filler.
[0019] In a preferred embodiment, in step S1, the average particle size of the carbon nanotubes is 50-100 nm.
[0020] In a preferred embodiment, in step S1, the mass ratio of the carbon nanotubes, anhydrous ethanol and potassium permanganate is 1:(200-400):(2-5).
[0021] In a preferred embodiment, in step S1, the reaction temperature is 50-70°C, and the reaction time is 4-6h.
[0022] In a preferred embodiment, in step S2, the average particle size of the carbon black is 50-100 nm.
[0023] In a preferred embodiment, in step S2, the mass ratio of the antioxidant, γ-glycidyloxypropyltrimethoxysilane, carboxylated carbon nanotubes and carbon black is 1:1:(0.5-1):(0.5-1).
[0024] In a preferred embodiment, in step S2, the temperature of the reflux reaction is 100-150° C., and the time of the reflux reaction is 2-4 h.
[0025] In a preferred embodiment, in step S2, the reaction is a reflux reaction, the reaction time is 4-8 hours, and the reaction temperature is 60-100°C.
[0026] The invention firstly carboxylates the carbon nanotubes and mixes them with carbon black having carboxyl groups on the surface thereof, firstly mixes an antioxidant and gamma-glycidyloxypropyltrimethoxysilane to react, so that the amino group on the antioxidant is grafted to one end of the gamma-glycidyloxypropyltrimethoxysilane, and then the other end of the gamma-glycidyloxypropyltrimethoxysilane is reacted and grafted with the carboxyl groups of the carbon nanotubes and the carbon black to form an antioxidant-coupling agent-filler structure, thereby improving the dispersibility of the carbon nanotubes and the carbon black, and when the antioxidant is grafted to the filler, the influence of the antioxidant on the stability of the rubber is prevented, and the two synergistically enhance the anti-aging and mechanical properties of the rubber.
[0027] This is mainly because carbon black can interact with rubber molecular chains through physical adsorption and chemical adsorption to improve the strength, hardness and wear resistance of rubber. Carbon nanotubes have extremely high aspect ratio and excellent mechanical properties, and they can be used as an efficient reinforcing material by themselves. When they co-exist in rubber, carbon black can be filled in the gaps between carbon nanotubes and between carbon nanotubes and rubber matrix. At the same time, carbon nanotubes can form a continuous network structure in the rubber matrix, playing a role similar to a skeleton, and carbon black particles can be attached to this skeleton to further enhance the mechanical properties of rubber, while carbon black and carbon nanotubes are mainly incompletely dispersed in rubber, and the present application improves dispersibility by grafting antioxidants. This is mainly the steric hindrance of the triphenylamine skeleton with tert-butyl as mentioned above, so the ability of the two to enhance the mechanical properties of rubber has been strengthened.
[0028] In addition, both carbon black and carbon nanotubes have a certain degree of thermal stability. Carbon black can absorb heat and, to a certain extent, prevent the thermal motion of rubber molecular chains. Carbon nanotubes can quickly disperse heat in the rubber matrix through their good thermal conductivity to prevent local overheating. At the same time, their interaction with rubber molecular chains can also inhibit the degradation and cross-linking reaction of rubber molecular chains at high temperatures, thereby improving the thermal stability of rubber.
[0029] In a preferred embodiment, the Mooney viscosity ML (1+8) of the brominated butyl rubber at 125° C. is 20-50.
[0030] The Mooney viscosity of the brominated butyl rubber defined in the present invention is low, its antioxidant performance is poor, its viscosity is low, and the stability of the brominated butyl rubber with low Mooney viscosity is poor. The carbon-bromine bond of the rubber is easily destroyed by antioxidants. The functional filler provided by the present invention enhances the viscosity of the brominated butyl rubber while enhancing its anti-aging performance and reducing the use of antioxidants.
[0031] This is mainly because carbon nanotubes have a high aspect ratio and a huge specific surface area. When added to rubber, at a low addition amount, carbon nanotubes can be evenly dispersed in the rubber matrix, and there is physical adsorption and entanglement between them and the rubber molecular chains. This interaction will restrict the movement of the rubber molecular chains, thereby increasing the viscosity of the rubber. At the same time, a network structure may also be formed between carbon nanotubes, further hindering the flow of rubber molecular chains, resulting in an increase in viscosity. When carbon black is added to rubber, the rubber molecular chains will be adsorbed on the surface of carbon black particles, so that the free movement of the rubber molecular chains is restricted. Moreover, carbon black particles will form agglomerates in rubber, and the presence of these agglomerates will also increase the resistance to rubber flow, thereby increasing the viscosity of the rubber. In addition, carbon black can be filled in the gaps between carbon nanotubes, and both carbon black particles and carbon nanotubes can interact with rubber molecular chains. This synergistic effect will restrict the movement of rubber molecular chains more strongly, and can more effectively increase the viscosity of rubber compared to adding carbon nanotubes or carbon black alone. In addition, the antioxidant grafted onto the functional filler is dispersed in a network structure, which has anti-aging properties and will not affect the stability of the rubber.
[0032] In a preferred embodiment, the rubber includes 5-12 parts by weight of the vulcanizing agent relative to 100 parts by weight of the brominated butyl rubber.
[0033] In a preferred embodiment, the vulcanizing agent includes zinc oxide and sulfur. Relative to 100 parts by weight of brominated butyl rubber, the content of zinc oxide is 3-8 parts by weight, and the content of sulfur is 2-4 parts by weight.
[0034] In a preferred embodiment, the rubber includes 0.5-5 parts by weight of the vulcanization accelerator relative to 100 parts by weight of the brominated butyl rubber.
[0035] In a preferred embodiment, the vulcanization accelerator is one or more of a thiuram accelerator, a dithiocarbamate accelerator and a sulfenamide accelerator.
[0036] In a second aspect, an embodiment of the present invention provides a method for preparing the above-mentioned high-performance aging-resistant rubber, comprising the following steps:
[0037] The brominated butyl rubber, antioxidant and functional filler are mixed once to obtain a masterbatch, and then the masterbatch is mixed with a vulcanizing agent and a vulcanization accelerator for a second time to obtain a rubber compound, and the rubber compound is vulcanized to obtain rubber.
[0038] In a preferred embodiment, the conditions of the primary mixing include: temperature of 60-90° C., rotation speed of 60-90 rpm, and time of 5-8 min.
[0039] In a preferred embodiment, the conditions for the secondary mixing include: temperature of 40-60° C., rotation speed of 30-60 rpm, and time of 3-5 min.
[0040] In a preferred embodiment, the vulcanization treatment conditions include: a vulcanization temperature of 140-190° C., a vulcanization pressure of 5-20 MPa, and a vulcanization time of 5-60 min.
[0041] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0042] 1. The present invention defines the above antioxidant, which is not easy to react with the rubber matrix due to the skeleton structure of the triarylamine, thereby improving the aging performance and enhancing the stability of the rubber.
[0043] 2. The present invention first carboxylates carbon nanotubes and mixes them with carbon black having carboxyl groups on the surface thereof, firstly reacts an antioxidant with γ-glycidyloxypropyltrimethoxysilane so that the amino group on the antioxidant is grafted to one end of the γ-glycidyloxypropyltrimethoxysilane, and then the other end of the γ-glycidyloxypropyltrimethoxysilane is reacted and grafted with the carboxyl groups of the carbon nanotubes and the carbon black to form an antioxidant-coupling agent-filler structure, thereby improving the dispersibility of the carbon nanotubes and the carbon black, and when the antioxidant is grafted to the filler, the influence of the antioxidant on the stability of the rubber is prevented, and the two synergistically enhance the anti-aging and mechanical properties of the rubber.
[0044] 3. The Mooney viscosity of the brominated butyl rubber defined in the present invention is low, its antioxidant performance is poor, its viscosity is low, and the stability of the brominated butyl rubber with low Mooney viscosity is poor. The carbon-bromine bonds of the rubber are easily destroyed by antioxidants. The functional filler provided by the present invention enhances the viscosity of the brominated butyl rubber while enhancing its anti-aging performance and reducing the use of antioxidants. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available.
[0047] Example 1
[0048] This embodiment provides a method for preparing high-performance aging-resistant rubber, comprising the following method:
[0049] By weight, 100 parts by weight of brominated butyl rubber having a Mooney viscosity ML (1+8) of 32 at 125° C. and 15 parts of functional fillers were mixed and kneaded at a temperature of 80° C. and a rotation speed of 80 rpm for 6 min to obtain a masterbatch, and then the masterbatch was mixed with 6 parts of zinc oxide, 3 parts of sulfur, and 2 parts of tetramethylthiuram disulfide at a temperature of 50° C. and a rotation speed of 40 rpm for 4 min to obtain a rubber compound, and the rubber compound was vulcanized at a temperature of 160° C. and a vulcanization pressure of 100 MPa for 30 min to obtain a rubber.
[0050] The preparation method of the functional filler is as follows:
[0051] S1, by mass, 1 part of carbon nanotubes with an average particle size of 60 nm was mixed with 300 parts of anhydrous ethanol, and dispersed evenly by ultrasonication for 10 min, and then the pH was adjusted to 4 with oxalic acid solution, and then 3 parts of potassium permanganate were added, and the mixture was reacted at 60° C. for 5 h to obtain carboxylated carbon nanotubes;
[0052] S2, by mass, 1 part of antioxidant and 1 part of γ-glycidyloxypropyltrimethoxysilane were mixed, and refluxed at 140°C for 3 hours, and then 0.5 parts of carboxylated carbon nanotubes and 0.5 parts of carbon black with an average particle size of 60 nanometers were added, and refluxed at 80°C for 6 hours, and then cooled and centrifuged to obtain a functional filler.
[0053] The antioxidant has a structure as shown in the following formula (1):
[0054]
[0055] The preparation method thereof is as follows:
[0056]
[0057] Take a 500 ml four-necked round-bottom flask and put in a stirrer and a reflux tube. After drying, fill it with nitrogen. Take the raw material sub-1 (51.28 mmol), raw material sub-2 (25.85 mmol), S-Phos (1.03 mmol), Pd 2 (dba) 3 (0.51mmol), sodium tert-butoxide (102.56mmol) were added to the flask, and then 200mL of toluene was added to the flask, and the mixture was stirred at 110°C for 2 hours. After the reaction was completed, the column liquid was passed through a silica gel flash column, and the column liquid was evaporated to a small amount of solvent, and 200mL of ethanol was added to precipitate to obtain the compound represented by formula (1), with a yield of 81%.
[0058] Elemental analysis: C 32 H 36 N 2O, theoretical value C, 82.72; H, 7.81; N, 6.03; O, 3.44; measured value C, 82.74; H, 7.82; N, 6.00.
[0059] HRMS (ESI) m / z [M+H] +: Calculated: 464.28; Found: 465.21.
[0060] Example 2
[0061] This embodiment provides a method for preparing high-performance aging-resistant rubber, comprising the following method:
[0062] By weight, 100 parts by weight of brominated butyl rubber having a Mooney viscosity ML (1+8) of 32 at 125° C., 3 parts of an antioxidant, and 15 parts of a functional filler are mixed and kneaded at a temperature of 80° C. and a rotation speed of 80 rpm for 6 min to obtain a masterbatch, and then the masterbatch is mixed with 6 parts of zinc oxide, 3 parts of sulfur, and 2 parts of tetramethylthiuram disulfide at a temperature of 50° C. and a rotation speed of 40 rpm for 4 min to obtain a rubber compound, and the rubber compound is vulcanized at a temperature of 160° C. and a vulcanization pressure of 100 MPa for 30 min to obtain a rubber.
[0063] The antioxidant has a structure as shown in the following formula (1):
[0064]
[0065] The preparation method thereof is as follows:
[0066]
[0067] Take a 500 ml four-necked round-bottom flask and put in a stirrer and a reflux tube. After drying, fill it with nitrogen. Take the raw material sub-1 (51.28 mmol), raw material sub-2 (25.85 mmol), S-Phos (1.03 mmol), Pd 2 (dba) 3 (0.51mmol), sodium tert-butoxide (102.56mmol) were added to the flask, and then 200mL of toluene was added to the flask, and the mixture was stirred at 110°C for 2 hours. After the reaction was completed, the column liquid was passed through a silica gel flash column, and the column liquid was evaporated to a small amount of solvent, and 200mL of ethanol was added to precipitate to obtain the compound represented by formula (1), with a yield of 81%.
[0068] Elemental analysis: C 32 H 36 N 2 O, theoretical value C, 82.72; H, 7.81; N, 6.03; O, 3.44; measured value C, 82.74; H, 7.82; N, 6.00.
[0069] HRMS (ESI) m / z [M+H] +: Calculated: 464.28; Found: 465.21.
[0070] The preparation method of the functional filler is as follows:
[0071] S1, by mass, 1 part of carbon nanotubes with an average particle size of 60 nm was mixed with 300 parts of anhydrous ethanol, and dispersed evenly by ultrasonication for 10 min, and then the pH was adjusted to 4 with oxalic acid solution, and then 3 parts of potassium permanganate were added, and the mixture was reacted at 60° C. for 5 h to obtain carboxylated carbon nanotubes;
[0072] S2, by mass, 1 part of antioxidant and 1 part of γ-glycidyloxypropyltrimethoxysilane were mixed, and refluxed at 140°C for 3 hours, and then 0.5 parts of carboxylated carbon nanotubes and 0.5 parts of carbon black with an average particle size of 60 nanometers were added, and refluxed at 80°C for 6 hours, and then cooled and centrifuged to obtain a functional filler.
[0073] Comparative Example 1
[0074] The difference between this comparative example and Example 2 is that the functional filler is changed to carbon nanotubes.
[0075] Comparative Example 2
[0076] The difference between this comparative example and Example 2 is that the functional filler is changed to carbon black.
[0077] Comparative Example 3
[0078] The difference between this comparative example and Example 2 is that the functional filler is changed to 0.5 parts of carboxylated carbon nanotubes and 0.5 parts of carbon black.
[0079] Comparative Example 4
[0080] The difference between this comparative example and Example 2 is that the preparation method of the functional filler is as follows:
[0081] S1, by mass, 1 part of carbon nanotubes with an average particle size of 60 nm was mixed with 300 parts of anhydrous ethanol, and dispersed evenly by ultrasonication for 10 min, and then the pH was adjusted to 4 with oxalic acid solution, and then 3 parts of potassium permanganate were added, and the mixture was reacted at 60° C. for 5 h to obtain carboxylated carbon nanotubes;
[0082] S2, by mass, 1 part of γ-glycidyloxypropyltrimethoxysilane, 0.5 parts of carboxylated carbon nanotubes and 0.5 parts of carbon black with an average particle size of 60 nanometers are refluxed at 80° C. for 6 hours, then cooled and centrifuged to obtain a functional filler.
[0083] Comparative Example 5
[0084] The difference between this comparative example and Example 2 is that the antioxidant is changed to antioxidant KY405, and the antioxidant used in the functional filler remains unchanged.
[0085] Comparative Example 6
[0086] The difference between this comparative example and Example 2 is that the antioxidant used in the functional filler is changed to antioxidant KY405.
[0087] Performance Testing
[0088] The hardness, tensile strength and tensile elongation of the rubber in the examples and comparative examples were tested with reference to GB / T528-2009. The results are shown in Table 1.
[0089] Thermal oxidative aging resistance: The rubber in the examples and comparative examples was placed in a drying oven at 160°C for continuous aging for 200 hours. The retention rate of tensile strength was tested with reference to GB / T528-2009. The calculation method was the percentage of the tensile strength after aging to the tensile strength before aging. The results are shown in Table 2.
[0090] Anti-ultraviolet aging: The rubber in the examples and comparative examples was irradiated with ultraviolet lamps with wavelengths of 200-275nm, 275-320nm and 320-400nm for 120h respectively, and the ultraviolet light intensity was 20W / cm 2 The distance between the sample and the ultraviolet light is 30 cm. The retention rate of tensile strength is tested according to GB / T528-2009. The calculation method is the percentage of the ratio of the tensile strength after aging to the tensile strength before aging. The results are shown in Table 2.
[0091] Table 1 Performance test results
[0092] Shore hardness / ShoreA Tensile strength / Mpa Tensile elongation / % Example 1 56 9.2 276 Example 2 58 9.3 283 Comparative Example 1 41 6.8 216 Comparative Example 2 40 6.6 210 Comparative Example 3 44 7.2 234 Comparative Example 4 48 7.6 254 Comparative Example 5 51 8.2 264 Comparative Example 6 49 7.9 259
[0093] Table 2 Performance test results
[0094]
[0095] From the above performance test results, it can be seen that the mechanical properties and aging resistance of the rubber of Examples 1-2 are relatively strong, especially the comprehensive performance of Example 2 is the most outstanding, which is mainly because the antioxidant grafting synergistic effect of the antioxidant and functional filler used in the present invention improves the mechanical properties and aging resistance of the rubber. The comparative example is obviously inferior to the example in the corresponding performance test because it does not adopt the necessary technical solution, which better proves the irreplaceable nature of the specific technical solution of the present application in achieving technical effects and solving technical problems.
[0096] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-performance aging-resistant rubber, characterized in that: Including bromobutyl rubber and antioxidant; Relative to 100 parts by weight of brominated butyl rubber, the content of the antioxidant is 0-5 parts by weight; The antioxidant is a phenolic antioxidant, and the phenolic antioxidant has at least a triphenylamine group in its structure.
2. The high performance aging resistant rubber according to claim 1, characterized in that: The rubber includes the functional filler in an amount of 10-20 parts by weight relative to 100 parts by weight of the brominated butyl rubber.
3. The high performance aging resistant rubber according to claim 2, characterized in that: The preparation method of the functional filler is as follows: S1, mixing carbon nanotubes with anhydrous ethanol, uniformly dispersing by ultrasonication, then adjusting the pH to 3-5 with oxalic acid solution, then adding potassium permanganate, and obtaining carboxylated carbon nanotubes after reaction; S2, mixing the antioxidant and γ-glycidyloxypropyltrimethoxysilane, and adding carboxylated carbon nanotubes and carbon black after reflux reaction, cooling and centrifuging after reaction to obtain a functional filler.
4. The high performance aging resistant rubber according to claim 3, characterized in that: In step S1, the average particle size of the carbon nanotubes is 50-100 nm; And / or, in step S1, the mass ratio of the carbon nanotubes, anhydrous ethanol and potassium permanganate is 1:(200-400):(2-5); And / or, in step S1, the reaction temperature is 50-70°C, and the reaction time is 4-6h.
5. The high performance aging resistant rubber according to claim 3, characterized in that: In step S2, the average particle size of the carbon black is 50-100 nm; And / or, in step S2, the mass ratio of the antioxidant, γ-glycidyloxypropyltrimethoxysilane, carboxylated carbon nanotubes and carbon black is 1:1:(0.5-1):(0.5-1); And / or, in step S2, the temperature of the reflux reaction is 100-150° C., and the time of the reflux reaction is 2-4 h; And / or, in step S2, the reaction is a reflux reaction, the reaction time is 4-8 hours, and the reaction temperature is 60-100°C.
6. The high performance aging resistant rubber according to claim 1, characterized in that: The Mooney viscosity ML (1+8) of the brominated butyl rubber is 20-50 at 125°C.
7. The high performance aging resistant rubber according to claim 1, characterized in that: The rubber comprises a vulcanizing agent in an amount of 5 to 12 parts by weight relative to 100 parts by weight of the brominated butyl rubber; The vulcanizing agent comprises zinc oxide and sulfur. With respect to 100 parts by weight of brominated butyl rubber, the content of the zinc oxide is 3-8 parts by weight, and the content of the sulfur is 2-4 parts by weight.
8. The high performance aging resistant rubber according to claim 1, characterized in that: The rubber comprises 0.5-5 parts by weight of a vulcanization accelerator relative to 100 parts by weight of brominated butyl rubber; The vulcanization accelerator is one or more of a thiuram accelerator, a dithiocarbamate accelerator and a sulfenamide accelerator.
9. A method for preparing the high-performance aging-resistant rubber according to any one of claims 1 to 8, characterized in that: The following steps are involved: The brominated butyl rubber, antioxidant and functional filler are mixed once to obtain a masterbatch, and then the masterbatch is mixed with a vulcanizing agent and a vulcanization accelerator for a second time to obtain a rubber compound, and the rubber compound is vulcanized to obtain rubber.
10. The method for preparing the high-performance aging-resistant rubber according to claim 9, characterized in that: The conditions of the primary mixing include: temperature of 60-90°C, rotation speed of 60-90rpm, and time of 5-8min; And / or, the conditions of the secondary mixing include: temperature of 40-60°C, rotation speed of 30-60rpm, and time of 3-5min; And / or, the vulcanization treatment conditions include: vulcanization temperature of 140-190° C., vulcanization pressure of 5-20 MPa, and vulcanization time of 5-60 min.
Citation Information
Patent Citations
Carbon nanotube doped ionic liquid modified butyl rubber elastomer and preparation method
CN109776979A
Anti-aging method of brominated butyl rubber
CN111019250A